Pengaruh Tingkat Pendidikan Formal Orang Tua terhadap Prestasi Belajar Mahasiswa Program Studi Bimbingan dan Konseling IKIP-PGRI Pontianak Tahun Akademik 2014/2015 - Eli Trisnowati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
This study uses fieldwork (Field Research), with a population of 150 students / i Prodi Counseling third semester of the academic year 2014/2015, which was divided into two groups: the experimental group (students who are high school level of education their parents / S1) totaled 30 people, and the control group (students whose parents education level SD) numbered 30 people. The results showed that no significant relationship between the level of formal education of parents on student achievement guidance and counseling courses Teachers' Training College PGRI Pontianak. This is shown by the price of